Dynamics behaviour of impacting water droplets on an inclined moving surface - Ong, Yee Ming (Nanyang Technological University, 2022)
The droplet impact dynamics have been extensively studied for centuries due to numerous industrial applications such as spray cooling and anti-icing on wind turbines. However, the droplet dynamic behaviours on a moving inclined surface have not been reported. Hence, this present study investigates the effect of various surface inclination and tangential velocities on a hydrophilic surface. Range of tangential velocities from 0 to 1.75 m/s and surface inclination of 0°, 30°,45°, and 60° were used in the experiment. The impingement process was captured with a digital high-speed camera (Phantom V711) and ImageJ software was used to process the videos frame by frame for analysis purposes. Thereafter, phenomenological observations and quantitative results in terms of maximum spreading factor Smax were presented. It was found that in the lower speed region, a higher inclination angle has the ability to reach larger Smax and vice versa. Furthermore, unique phenomena were observed at specific conditions: (a) For 45° inclination angle, the partial rebound of the droplet is observed for tangential We ≥ 35. (b) For 60° inclination angle at tangential We = 0, the droplet undergoes receding breakup and forms a secondary droplet due to extreme thinning of the liquid film.